Use of modern technologies for promoting health at the population level in India - Rukman Manapurath; Deepthi Raran Veetil; Mohan S. Kamath (The Lancet Regional Health - Southeast Asia, 2024)
Health Technology Assessment (HTA) evaluates the technologies, influencing healthcare policy and improving health outcomes
Keywords: Health financing; Public health; Health insurance